Outcome determinants of pterional surgery for tuberculum sellae meningiomas - (:unkn) unknown (SPRINGER WIEN, 2005)
Background. Current literature on tuberculum sellae meningiomas is very heterogenous due to wide variation in nomenclature, diagnostic and operative techniques. The aim of this study is specifically to analyze the results of pterional craniotomy for tuberculum sellae meningiomas. A homogenous cohort of 42 consecutively operated tuberculum sellae meningioma cases are reviewed with special emphasis on the effects of pterional microsurgery on visual outcome. Methods. This is a retrospective clinical analysis. 42 consecutive patients operated upon during the period of 15 years in a single institution using standard imaging protocols and pterional microsurgery are presented and effect of various variables on visual outcome analysed. Findings. 81% of the patients presented with visual symptoms. The mean duration of symptoms was 12 months. Tumour volumes ranged from 7.5 to 210 mm(3). A right sided pterional microsurgery was used in all patients. Complete resection rate was 81%. Vision improved in 58%, worsened in 14%. Non-visual morbidity was 7.1% and mortality was 2.4%. The follow up period of patients ranged from 3 to 192 months ( median: 30 months). The mean was 37.5 months (SD +/- 36.7 months) and a recurrence rate of 2.4% was observed. Conclusions. A standard pterional craniotomy using microsurgical technique provides the necessary exposure enabling total removal while keeping the complications to a minimum. Upon analysis of our findings we found that patient age of more than 60, duration of visual symptoms longer than 1 year, severe visual symptomatology, predominantly vertical growth, presence of significant peri-tumoural oedema, absence of an intact arachnoid plane and subtotal removal were correlated with a dismal visual outcome.
Keywords: meningioma; tuberculum sellae; pterional craniotomy; visual impairment; GROWTH-FACTOR EXPRESSION; SUPRASELLAR MENINGIOMAS; MICROSURGICAL MANAGEMENT; SURGICAL-MANAGEMENT; VISION; REGION; SERIES; EDEMA